Electrochemistry of modified graphene and carbon nanomaterials - Poh, Hwee Ling (2015)
This thesis investigates the various methods adopted to improve graphene and their influences on the properties of the obtained material. The study is divided into three parts: a) Part 1: Influence of heteroatom functionalization on the properties of graphene, b) Part 2: Influence of synthesis methods/conditions on the properties of graphene and c) Part 3: Influence of structural differences on the properties of nanocarbons. The thesis will begin by introducing graphene, its history and development over the years in Chapter 1. Following which, Chapter 2 will review in depths of recently published impactful literature articles that are related to the three parts. Before proceeding, Chapter 3 will re-emphasize the readers on the objectives of this thesis with a summarized infographical diagram of each part. Chapters 4 – 8 will present research results that conceptualize on Part 1: Influence of heteroatom functionalization on the properties of graphene. An array of different heteroatom dopants were investigated with full-scale characterization of the doped materials. Chapters 9 – 10 will analyze Part 2, i.e how different synthesis methods and conditions may influence the properties of the final products. Chapter 11 analyzes Part 3 to evaluate the properties of nanocarbons that are structurally different. Lastly, Chapter 12 will provide an overview of the chapters and concludes the thesis.